Influence of tour operator’s sustainability practices on tourists’ spending and trip duration - Ronoh, Kipchirchir Samuel; Kipkosgei, Bitok; Ndolo, Urbanus Mwinzi; Mutiga, Marciano; Chemutai, Nancy (Goodwood Publishing, 2025)
Purpose: This study examines how sustainability practices influence tourists' propensity to spend more time and extend their stay. Research Methodology: The study involved 114 tour firms and 342 tourists in Nairobi City County, Kenya. Tour operators' sustainability adoption levels were categorized using Z-scores from a compliance checklist, while tourist behavior was assessed through questionnaires. General Linear Models (GLM) were used to analyze the relationship between adoption levels and tourist behavior. Results: The findings of the study reveal that higher levels of sustainability - specifically Very High (VH), high (H), and moderate (M)–are positively associated with increased spending and longer stays. In contrast, low (L) and Very Low (VL) sustainability levels did not significantly affect these behaviors. Limitations: The use of Z-scores for categorization reduces complex data to a single dimension, which may oversimplify subtle differences in the adoption of sustainability practices among tour operators. Contribution: These results offer valuable insights for tour operators and stakeholders, demonstrating that integrating sustainability into business operations not only benefits the environment and local cultures, but also enhances economic outcomes for businesses and destinations.